2009
DOI: 10.5539/jsd.v2n2p148
|View full text |Cite
|
Sign up to set email alerts
|

Some Common Non-Timber Forest Products Traded by Indigenous Community in Sabah, Malaysia

Abstract: The survey showed that a total number of 109 species of NTFPs were traded locally in the tamu (open market), comprising 35 species of wild edible plants, 32 species of medicinal plants, 8 species of orchids, 4 species of bamboos, 6 species of rattans, 8 species of fish, 8 species of wild fruit trees and 8 species of other products. This survey covered ten most common tamu and major ethnic groups in Sabah, mainly Kadazandusun, Rungus and Murut.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Knowledge of and respect for traditional foods and the use of a range of plants for medicinal purposes is commonplace among older village people but also widespread among rural outmigrants. Recent research on the trading of nontimber forest products by indigenous people in 10 open markets in Sabah showed that a wide range of edible and medicinal plants, flowers and other materials was traded (Kodoh et al, 2009). This suggests that plants for medicinal use have a wide market with suitable publicity among city-dwelling rural migrants and others believing in alternative medication.…”
Section: Change In Rural Malaysia In Recent Decadesmentioning
confidence: 99%
“…Knowledge of and respect for traditional foods and the use of a range of plants for medicinal purposes is commonplace among older village people but also widespread among rural outmigrants. Recent research on the trading of nontimber forest products by indigenous people in 10 open markets in Sabah showed that a wide range of edible and medicinal plants, flowers and other materials was traded (Kodoh et al, 2009). This suggests that plants for medicinal use have a wide market with suitable publicity among city-dwelling rural migrants and others believing in alternative medication.…”
Section: Change In Rural Malaysia In Recent Decadesmentioning
confidence: 99%
“…The ovary is slender, hairy and approximately 5 mm long. The drupes are somewhat globose, green, and comprise a woody endocarp approximately 5 cm across (Figure 1) carved with blood vessel-like lines sheltering a pungent, spongy, and oily seed with the size and appearance of a somewhat light brown ping pong ball [21]. The transversal section of the germinating seeds presents purple patches (personal observation).…”
Section: Resultsmentioning
confidence: 99%
“…A phytochemical analysis of the leaves resulted in the identification of lucenin-2 (luteolin 6,8-di-C-glucoside) (18), vicenin-2 (apigenin 6,8-di-C-glucoside) (19), isoschaftoside (apigenin 6-C-arabinosyl-8-C-glucoside) (20), tricin 7-O-glucoside (21), and isorhamnetin 3-O-robinobioside (22) [62] (Figure 2). Lucenin-2 (18) inhibited the growth of P. aeruginosa (ATCC 27853), E. coli (ATCC 11229), and K. pneumoniae (ATCC 27736) with the MIC values of 8, 64, and 64 µg/mL, respectively [38].…”
Section: Flavonoid Glycosidesmentioning
confidence: 99%
“…Edible vegetable is among products collected from the forest by indigenous people of the island (Hastin et al, 2013). Vegetable for consumption are also found cultivated in home gardens and sold in local markets (Kodoh et al, 2009;Kamarul et al, 2012;Hastin et al, 2013;Foo et al, 2016;Jualang et al, 2016). The significant of vegetable is not just as food sources, but also important for cultures, income generation, and scientific studies (Kodoh et al, 2009;Normiadilah and Noriah, 2012;Hastin et al, 2013;Wan Izatul, 2013;Solehah and Nasuruddin, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Intake of polyphenols diet could help prevent many illnesses that are related to free radical damage such as neurodegenerative diseases, cancers, and cardiovascular-related illnesses (Tsao, 2010). The vegetable also served a commercial purpose in generating income, as vegetable can be harvested from the local forest and traded in markets or produce in industrial scale farm for larger markets import (Kodoh et al, 2009;Hastin et al, 2013;Foo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%